2003
DOI: 10.1007/bf03345243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GH replacement on metabolism and physical performance in GH deficient adults

Abstract: GH deficiency (GHD) in adults is associated with abnormalities in body composition, metabolic derangements, sub-optimal physical performance, high incidence of adverse cardiovascular risk factors and poor quality of life. GHD adults are insulin resistant and have reduced hepatic glycogen stores, reduced insulin stimulated glucose utilization and reduced glycogen synthesis in muscle. GH replacement results in either no change or slight reduction in insulin sensitivity. Hence, it is important to monitor for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
2
11
0
1
Order By: Relevance
“…Adult patients with growth hormone deficiency are predisposed to premature atherosclerosis and other cardiovascular diseases (Twickler et al, 2000;Elhadd et al, 2001). Growth hormone replacement in GH-deficient adult patients improves their LDL-cholesterol abnormalities (Twickler et al, 2000;Abdul Shakoor and Shalet, 2003). Therefore, growth hormone also prevents atherosclerosis and other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients with growth hormone deficiency are predisposed to premature atherosclerosis and other cardiovascular diseases (Twickler et al, 2000;Elhadd et al, 2001). Growth hormone replacement in GH-deficient adult patients improves their LDL-cholesterol abnormalities (Twickler et al, 2000;Abdul Shakoor and Shalet, 2003). Therefore, growth hormone also prevents atherosclerosis and other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In acromegalic patients, excess GH does not result in increased muscle mass or strength (21)(22)(23), while the observed increase in muscle strength and endurance experienced by GHD patients following GH treatment appear to be a result of altered metabolic functions as well as a stimulation of protein synthesis, suppression of protein oxidation and increased muscle mass (24)(25)(26)(27). Taken together, it is currently not clear whether GH/IGF1 and skeletal muscle myofibrillar protein synthesis are positively correlated in man, but investigating both acromegalic and GHD patients offers a unique possibility to address this question.…”
Section: Introductionmentioning
confidence: 97%
“…GH has important physiological functions in adult humans and several studies have shown that GHD in adult patients is associated with abnormalities in body composition, visceral obesity, metabolic derangements and impaired physical performance (2 -7). These impairments improve with recombinant human GHreplacement therapy (rhGH) (2,4,6,(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%